Ladder‐Type Heteroheptacenes with Different Heterocycles for Nonfullerene Acceptors. Issue 48 (15th September 2020) - Ma, Yunlong; Cai, Dongdong; Wan, Shuo; Wang, Pengsong; Wang, Jinyun; Zheng, Qingdong
Abstract: The design, synthesis, and characterization of two novel nonfullerene acceptors (M8 and M34) based on ladder‐type heteroheptacenes with different heterocycles are reported. Replacing the furan heterocycles with the thiophene heterocycles in the heteroheptacene backbone leads to a hypsochromically shifted absorption band and greatly improved carrier transport for the resulting nonfullerene acceptor (M34) although the π–π‐stacking distances are barely affected. Bulk‐heterojunction polymer solar cells fabricated from M34 and a wide band gap polymer (PM6) as the donor showed a best power conversion efficiency (PCE) of 15.24 % with an open circuit voltage (VOC ) of 0.91 V, much higher than a PCE of 4.21 % and a VOC of 0.83 V for the counterparts based on M8:PM6. These results highlight the importance of key atoms in the construction of high‐performance nonfullerene acceptors. Abstract : Substitutions of oxygen atoms with sulfur atoms in the ladder‐type heteroheptacene core boost the power conversion efficiency of nonfullerene acceptor from 4.21 % to 15.24 %. This result suggests the importance of key atoms in the conjugated backbone of nonfullerene acceptors, which can significantly affect their energy levels, band gap, charge transport, charge separation, and photovoltaic properties.